La gestión de la liquidez del Banco Central Europeo durante la crisis financiera: 2008 - 2009 - Carlos Pateiro Rodríguez; Jesús M. García Iglesias; Ramón Nu\~nez Gamallo (Colegio de Economistas de A Coru\~na, 2010)
– After the bankruptcy of Lehman Brothers, in September 2008, there was huge stress in the financial markets. In the money markets, the Eurosystem had to adopt measures providing liquidity to banks in order to avoid the collapse of the interbank market. In this work we analyze the changes in the ways of injecting liquidity in the system, within a context of serious economic and financial crisis. With decreasing interest rates, there had been a radical transformation between October 2008 and mid 2009. The longer-term refinancing operations reached the first position, removing the main refinancing operations, while was enlarged the list of securities as collateral, and an increasing number of banks resorted to liquidity auctions. If the ECB decides to limit longer-term financing auctions, adapting them to its usual monetary policy procedure, it will be of great interest the analysis of the current debt of the banks with respect to the ECB.
Keywords: E43; E52; E58; 330; Eurosistema; operaciones de mercado abierto; tipos de interés; inflación; Eurosystem; open market operations; interest rates; inflation